Pengaruh Loan to Deposit Ratio Dan Biaya Operasional Pendapatan Operasional Terhadap Profitabilitas Bank - Bella Aldama Faradilla; Filani Zikri Hassan; Soei Khim (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
Profitability is the ability or ability of banks to make a profit. The problem of profitability is very important because bank revenue is the main target that must be achieved by the bank because the main goal of the bank is to achieve profit. The higher the bank's profitability, the better the bank's performance. The formulation of the problem in this study are does the Loan to Deposit Ratio (LDR) affect profitability, Operational Income Operational Costs (BOPO) affect profitability and Loan to Deposit Ratio and Operational Income Operational Costs affect Profitability. Public Bank for the 2014-2019 period. Data were analyzed using the classic assumption test, multiple linear regression analysis, Determination analysis, simultaneous significance test (F test) and partial significance test (t-test). The results showed that the Loan to Deposit Ratio had a negative and significant effect on Profitabiltas. Operating Costs Operating Income has a negative and significant effect. Loan to Deposit Ratio and Operating Costs Operating Income has effect on profitability at commercial banks for the 2014-2019 period. Keywords : LDR, BOPO and profitability